Analisis Kasus Wanprestasi Dalam Transaksi Jual Beli Secara “Online” - Ramadhani, Dwi Aryanti; Dewani, Citranti Hanifah; Nurhayati, Elsa; Zaini, Noer Gita Safira; Rahmadhani, Swastika (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Agreements in e-commerce and ordinary agreements are not much different, the only difference is the form and application. Default is a term taken from the Dutch word wanprestatie which means failure to fulfill achievements or obligations in an agreement. In this study the author analyzes the court decision regarding default in online / e-commerce sales and purchase agreements, namely Decision Number 629/Pdt.G/2020/PN JKT.SEL